The Preparation and Characterization of Chitosan / Poly (Vinyl Alcohol) Blended Films - El-Hefian, E.A.; Nasef, M.M.; Yahaya, A.H. (Hindawi Publishing Corporation, 2010)
In this study, chitosan and PVA were blended at different proportions (considering chitosan as the main component) in solution forms. The chemical structure and the morphology of the obtained blend films were investigated using FTIR and field emission scanning electron microscope (FESEM). The thermal stability of the blend films were also studied using thermal gravimetric analysis (TGA). Our results showed that chitosan and PVA form a compatible blend and their films displayed homogenous and smooth surface properties compared to their individual pure components. The blending of PVA with chitosan at all proportions was found to highly enhance the swelling of the obtained films compared to that of pure chitosan one.